Factors associated with the performance and achieving goals of specialized periodontal procedures in Brazilian dental specialties centers - Raíres Chaves da Silva Rodrigues; Yuri Wanderley Cavalcanti; Edson Hilan Gomes de Lucena (BMC, 2024)
Abstract Background The Brazilian Dental Specialty Centers (CEO, in Portuguese) represent the strategy of the National Oral Health Policy to provide secondary-level dental care. They offer more complex procedures, such as the treatment of periodontitis. This study aims to investigate the factors associated with the performance and the achievement goals of specialized procedures and the achievement gols of periodontics in CEO. Methodology Analytical and cross-sectional study using secondary data. The database of the second cycle of the External Evaluation of the National Program for Improving Access and Quality in CEO (PMAQ-CEO, in Portuguese), was utilized, which assessed 1,042 CEO on-site in 2018. The data were analyzed using multiple Poisson regression, estimating the prevalence ratio (PR) (p < 0.05). Results A third of the CEO (n = 305) performed all specialized procedures, with a higher prevalence observed in those with more than one bicarbonate jet prophylaxis unit (RP = 2.12; 95% CI: 1.160-3.881; p = 0.015) and when they had a higher percentage of specialist professionals (RP = 1.004; 95% CI: 1.002-1.006; p < 0.001). The periodontics goal was achieved by 617 (59.2%) CEO, with a higher prevalence among those who had a manager with supplementary training (PR = 1.21; 95% CI: 1.100-1.335; p < 0.001) and with a higher workload for the periodontist dentist (PR = 1.15; 95% CI: 1.103-1.201; p < 0,001). Conclusion Although most CEOs do not perform allspecialized periodontics procedures, more than half achieved the established goals. The provision of specialized periodontics services in CEO and the achievement of goals are influenced by the quantity and professional qualifications, as well as the availability of equipment.